2019
DOI: 10.1111/dmcn.14225
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric measurements to identify undernutrition in children with cerebral palsy

Abstract: AIM To evaluate the diagnostic performance of anthropometric indicators to identify undernutrition in children with cerebral palsy (CP). METHODThe present study was a monocentric retrospective analysis of prospectively collected data among children and adolescents with CP participating in a rehabilitation program. Undernutrition was defined as a z-score for dual-energy X-ray absorptiometry (DXA) determined body fat percentage less or equal to À2.0. The cut-off values for body mass index (BMI) of the World Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…There are also several clinical conditions or disorders in which it has been shown that the correlation between DXA and BMI Z-score is not satisfactory, such as in patients with Down syndrome [13] in whom the BMI underestimates the alteration of the fat percentage in up to 57% of cases. Likewise, the study by Duran et al [15], in children with cerebral palsy, showed that the BMI Z-score overestimated the prevalence of underweight. In addition, a study on the accuracy of the BMI Z-score for detecting changes in fat percentage after a therapeutic intervention showed that this parameter had low specificity and, therefore, was not a solid predictor of adiposity change [12].…”
Section: Comparison With the Literaturementioning
confidence: 90%
See 3 more Smart Citations
“…There are also several clinical conditions or disorders in which it has been shown that the correlation between DXA and BMI Z-score is not satisfactory, such as in patients with Down syndrome [13] in whom the BMI underestimates the alteration of the fat percentage in up to 57% of cases. Likewise, the study by Duran et al [15], in children with cerebral palsy, showed that the BMI Z-score overestimated the prevalence of underweight. In addition, a study on the accuracy of the BMI Z-score for detecting changes in fat percentage after a therapeutic intervention showed that this parameter had low specificity and, therefore, was not a solid predictor of adiposity change [12].…”
Section: Comparison With the Literaturementioning
confidence: 90%
“…However, some studies state that the BMI Z-score has low sensitivity for the detection of excess adiposity in children [11][12][13][14][15]. It may not be an ideal tool in some situations involving altered body composition [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the great risk of malnutrition, there are no recommended methods for assessing nutritional risks in children with CP in Denmark. Several studies outside of Denmark have examined, validated and evaluated the ability of screening tools, anthropometric measurements, growth curves and questionnaires to identify malnutrition among this target group of children (11)(12)(13)(14)(15)(16)(17)(18) . In 2017, The European Society for Pediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) determined the evidence from the literature, combined it with recommendations from experts, and developed 31 recommendations and suggestions for professionals working with children with physical and mental disabilities, including CP (9) .…”
mentioning
confidence: 99%